1982
DOI: 10.1159/000123388
|View full text |Cite
|
Sign up to set email alerts
|

Foot Shock Analgesia

Abstract: Effects of inescapable foot shock on pain threshold and on levels of immunoreactive β-endorphin (ir-βEP) in anterior pituitary, neuro-intermediate lobe and plasma were determined by hot plate test and radioimmunoassay respectively. Whereas handling and conditioned stress failed to alter baseline pain threshold, 20 min inescapable foot shock produced modest and transient analgesia. Levels of plasma ir-βEP and corticosterone were significantly and concurrently raised by all treatments and remained elevated 40 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The degree of stress-induced analgesia (Wolfle and Liebeskind 1983) that might be associated with such increased peripheral plasma {3-EP I -31 levels in the lamb was not assessed in these preliminary experiments. Increased levels of {3-EP may not always be correlated with the degree of induced analgesia, for example, after footshock in rats (Lim et al 1982b) or after acupuncture in horses (Bossut et al 1983), although {3-EP I -31 has been shown to be a potent analgesic by intravenous injection (Tseng et al 1976;Feldberg and Smyth 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of stress-induced analgesia (Wolfle and Liebeskind 1983) that might be associated with such increased peripheral plasma {3-EP I -31 levels in the lamb was not assessed in these preliminary experiments. Increased levels of {3-EP may not always be correlated with the degree of induced analgesia, for example, after footshock in rats (Lim et al 1982b) or after acupuncture in horses (Bossut et al 1983), although {3-EP I -31 has been shown to be a potent analgesic by intravenous injection (Tseng et al 1976;Feldberg and Smyth 1977).…”
Section: Discussionmentioning
confidence: 99%